The Influence of Product Quality, Brand Image, Digital Marketing, and Human Resource Competence on Purchase Intention - Jenny M. Simanjuntak; Anita Tresia Samosir; Gloria J.M. Sianipar (Manunggal Halim Jaya, 2026)
The digital era offers substantial opportunities for micro, small, and medium enterprises (MSMEs) to access broader markets and expand their businesses. However, Gambir Tea MSMEs face challenges as product sales have not yet reached their optimal level. These challenges stem from limited consumer awareness of product quality and benefits, weak brand recognition that hinders the development of a strong brand image, and insufficient utilization and mastery of digital technologies, all of which ultimately affect purchase intention. Such conditions pose significant challenges for Gambir Tea MSMEs that rely heavily on consumer purchase intention to sustain and grow their businesses. This study aims to examine the effects of product quality, brand image, digital marketing, and human resource competence on purchase intention among Gambir Tea MSMEs in Pakpak Bharat Regency, Indonesia. An explanatory research design with a quantitative approach was employed, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that product quality, brand image, and digital marketing have positive and significant effects on purchase intention. In contrast, human resource competence does not have a significant effect on purchase intention. This study contributes theoretically by extending the relational marketing framework. It provides practical insights for MSMEs on developing sustainable purchase intentions through improved product quality, stronger brand image, and effective digital marketing strategies focused on consumer satisfaction.